Anti-ganglioside complex antibodies in Miller Fisher syndrome. Issue 9 (13th April 2006) - Kaida, K; Kanzaki, M; Morita, D; Kamakura, K; Motoyoshi, K; Hirakawa, M; Kusunoki, S
Abstract : Background: Some ganglioside complexes (GSCs) are target antigens for serum antibodies in patients with Guillain–Barré syndrome (GBS). Anti-GSC antibodies may be associated with particular clinical features of GBS. Objective: To investigate antibodies to GSCs in the sera of patients with Miller Fisher syndrome (MFS) characterised by elevation of the IgG anti-GQ1b antibody. Results: In all, 7 of 12 (58%) consecutive patients with MFS were found to have IgG antibodies to GSCs containing GQ1b, of whom 5 had IgG antibodies to GQ1b-GM1 complex (GQ1b/GM1) and 2 had antibodies to GQ1b/GD1a; 4 of 5 patients without sensory symptoms had anti-GQ1b/GM1 antibodies. Conclusions: At least three different specificities in MFS-associated antibodies, GQ1b-specific, anti-GQ1b/GM1-positive and anti-GQ1b/GD1a-positive, were observed. In patients with MFS not only GQ1b itself but also clustered epitopes of GSCs, including GQ1b, may be considered to be prime target antigens for serum antibodies. A tendency to escape sensory disturbances is shown by anti-GQ1b/GM1-positive MFS.